RAD51 protects against nonconservative DNA double-strand break repair through a nonenzymatic function. Issue 5 (8th February 2022) - So, Ayeong; Dardillac, Elodie; Muhammad, Ali; Chailleux, Catherine; Sesma-Sanz, Laura; Ragu, Sandrine; Le Cam, Eric; Canitrot, Yvan; Masson, Jean Yves; Dupaigne, Pauline; Lopez, Bernard S; Guirouilh-Barbat, Josée
Abstract: Selection of the appropriate DNA double-strand break (DSB) repair pathway is decisive for genetic stability. It is proposed to act according to two steps: 1-canonical nonhomologous end-joining (C-NHEJ) versus resection that generates single-stranded DNA (ssDNA) stretches; 2-on ssDNA, gene conversion (GC) versus nonconservative single-strand annealing (SSA) or alternative end-joining (A-EJ). Here, we addressed the mechanisms by which RAD51 regulates this second step, preventing nonconservative repair in human cells. Silencing RAD51 or BRCA2 stimulated both SSA and A-EJ, but not C-NHEJ, validating the two-step model. Three different RAD51 dominant-negative forms (DN-RAD51s) repressed GC and stimulated SSA/A-EJ. However, a fourth DN-RAD51 repressed SSA/A-EJ, although it efficiently represses GC. In living cells, the three DN-RAD51s that stimulate SSA/A-EJ failed to load efficiently onto damaged chromatin and inhibited the binding of endogenous RAD51, while the fourth DN-RAD51, which inhibits SSA/A-EJ, efficiently loads on damaged chromatin. Therefore, the binding of RAD51 to DNA, rather than its ability to promote GC, is required for SSA/A-EJ inhibition by RAD51. We showed that RAD51 did not limit resection of endonuclease-induced DSBs, but prevented spontaneous and RAD52-induced annealing of complementary ssDNA in vitro . Therefore, RAD51 controls the selection of the DSB repair pathway, protecting genome integrity from nonconservative DSB repair through ssDNA occupancy, independently of the promotion of CG.